(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The article presents materials on the study of biological absorption coefficients of oleaster, beets, radishes, carrots, which have high rates of biological absorption coefficient in relation to Se, Pb, Zn. It is also given that these plants are concentrators for these elements and they can be used from this point of view.